A Comparison Effect Of feeding Barley or Soybean Meal Chemically Treated As A Source Of Undegradable Protein in Milk Production and Composition in Awassi Ewes - Mohammed, Omar Dheyaa; Abdullah, Mohammed Najim; Abbo, Nadir Yousef; Salih, Nashwan Nather (Journal of agricultural, environmental and veterinary sciences, 2020)
This study was conducted in animal research department at Ministry of Agriculture , by using 21 Awassi ewes with single lambs , after two weeks of birth , the average body weight 60.90 ± 1.92 kg and ages 3- 5 years. The ewes were divided into three groups , which was fed ad libitum on the experimental rations , first group (T1) was fed on control ration consist of barley grain , wheat bran , soybean meal and wheat straw which contained 13.46% crud protein , second (T2) and third (T3) group were fed on ration consist neither slow degradable barley grain nor slow degradable soybean meal as a source of undegradable protein and contained 16% crud protein , All ration was iso calorie and iso degradable protein. Results was indicated to a significant (p<0.05) increased in milk yield in T2 1504 g/day compared to T1 and T3 which was 1155 and 1151 g/ day, milk components dose not differed significantly between treatments , but it was noted significant increase in lactose yield 88.30 g/ day and energy yield 1229 kcal/ day in T2 compared T1 and T3 which were 65.33 , 67.29 g/ day and 874 , 881 kcal/ day respectively , the differences were not in final ewes body weight or in average daily gain of lambs , blood glucose concentration decreased (p<0.05) in T2 54.40 mg/dl as compared to T1 76.29 mg/ dl and T3 71.10 mg/ dl , while the differences were not significant in the other blood parameters.